Effects of Coronavirus Disease 2019 (COVID-19) on Peripheral Blood Lymphocytes and Their Subsets in Children: Imbalanced CD4+/CD8+ T Cell Ratio and Disease Severity - Mahmoudi, Shima; Yaghmaei, Bahareh; Sharifzadeh Ekbatani, Meisam; Pourakbari, Babak; Navaeian, Amene; Parvaneh, Nima; Haghi Ashtiani, Mohammad Taghi; Mamishi, Setareh (Frontiers in Pediatrics, 2021)
Introduction: Although the pathogenesis of Coronavirus Disease 2019 (COVID-19) is not fully described and the interaction between the SARS-CoV-2 and the immune system is complicated, lymphopenia, hyper-inflammatory responses, and cytokines play an essential role in the pathology of COVID-19. Some hematological abnormalities have been described among the laboratory features of COVID-19. However, no studies about lymphocyte subset analyses have been reported in children. Therefore, this study aimed to explain the characteristics of lymphocyte subsets in pediatric patients with mild or severe COVID-19. Methods: The study’s subjects were children with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pneumonia confirmed with real-time RT-PCR. The study’s subjects were admitted to the Children's Medical Center, affiliated with the Tehran University of Medical Sciences, between March 7th and June 10th of 2020. Complete blood counts and lymphocyte subpopulations were studied for all patients. Results: The study population included 55 hospitalized patients with confirmed SARS-CoV-2 infection (34 patients (62%) with a mild form of the disease and 21 patients (38%) with a severe form). Lymphocyte counts were significantly lower in patients with the severe form (mean± sd 1.6± 0.9 in the severe group vs. 2.3± 2.2 in the mild group). Compared with mild pneumonia, children with severe pneumonia had a higher count of CD8+ lymphocyte and a lower percentage of CD4+ lymphocyte. However, the differences were not significant. Interestingly, the severe group had a significantly lower CD4+/CD8+ T cell ratio compared to the mild group (1.1 ± 0.47 vs. 1.4 ± 0.8, p-value: 0.039). CD4+/CD8+ less than 2, 1.5, and 1 was found in 48 (87%), 40 (73%), and 19 cases (35%). Among 7 cases (13%) who died, 100% had CD4+/CD8+ ratio of <2, 86% had CD4+/CD8+ ratio of <1.5, and 29% had CD4+/CD8 + ratio of <1. Conclusion: A decrease in CD4+/CD8+ ratio indicates the extent of the impairment of the immune system by COVID-19. Therefore, a decline in CD4+/CD8+ 8 ratio may serve as a useful factor to reflect the derangement of immune responses and even death in patients with severe COVID-19.